Observer based chaos synchronization and its application to secure communication - WANG Xing-yuan; DUAN Chao-feng (Tongxin xuebao)
A linear state observer based synchronization scheme for a class of chaotic systems was presented, and this scheme was applied to secure communication. The analysis result to the observer showed that the system’s convergence rate of the synchronization error depends on the parameter θ of observer gain, in the sense that the larger the value of θ, the faster the convergence. Finally, a simulation of R?ssler system effectively exploits the proposed scheme’s effectiveness.